A method for preparing a reaction sintered silicon nitride substrate
Patent Information
- Application Number
- CN202610473409.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-10
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-04-10
AI Technical Summary
然而,通过这些方法提高氮化硅基板热导率的同时,基板的弯曲强度降低,不利于其在IGBT模块恶劣的热环境中应用
1.本发明在碳源中引入改性纳米球形碳粉。首先,相较于常规碳粉,纳米球形碳粉的粒度和含氧量低,活性高,能与氮化硅陶瓷二相反应,消除部分多余二相,提高热导率。其次,对纳米球形碳粉接枝双氨基硅烷,提高其与浆料的界面相容性,进而提高流延工艺中浆料的流动性,降低对流延工艺的不利影响。最后,改性纳米球形碳粉与硅粉和助烧结剂的界面结合力增强,提高还原氮化反应速率,降低基板内部缺陷,提高基板致密度和力学性能。
Smart Images

Figure CN122212776B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of silicon nitride substrate technology, specifically a method for preparing a reaction-sintered silicon nitride substrate. Background Technology
[0002] Insulated-gate bipolar transistors (IGBTs) are core semiconductor power devices for energy conversion and transmission, often referred to as the "CPU" of power electronic devices. They are widely used in rail transportation, smart grids, ultra-high voltage power transmission, and new energy electric vehicles. Small size and high integration density devices are key to efficient energy utilization, significantly reducing power module energy consumption and failure rates, but they also generate severe thermal stress. Silicon nitride ceramics, due to their excellent heat dissipation capabilities and thermal shock resistance, have become one of the most suitable materials for high-power module packaging.
[0003] Reaction-sintered silicon nitride ceramics are a unique type of silicon nitride ceramic with extremely high thermal conductivity, providing greater reliability for high-power modules. The theoretical thermal conductivity of silicon nitride ceramics can exceed 200 W / m•K; however, achieving values above 110 W / m•K in actual manufacturing is challenging. To effectively improve thermal conductivity, the following strategies are commonly employed: First, high-purity silicon powder is a prerequisite for preparing high-thermal-conductivity silicon nitride ceramics. Second, larger-particle-size silicon nitride grains are selected to reduce secondary phases and lower the lattice oxygen content within the silicon nitride grains. Third, low nitrogen pressure, higher nitriding temperature, and a larger proportion of β-phase nitride contribute to the formation of sintered bodies with higher thermal conductivity in the post-sintering stage. Fourth, during reaction sintering, the introduction of sintering aids such as magnesium silicon nitrides, lithium oxide, ytterbium oxide, metals, zirconium oxide, and carbon sources helps to form sintered bodies with even higher thermal conductivity. However, while these methods improve the thermal conductivity of silicon nitride substrates, they also reduce the substrate's bending strength, which is detrimental to its application in the harsh thermal environment of IGBT modules.
[0004] Therefore, the present invention has developed a reaction-sintered silicon nitride substrate with high thermal conductivity and high bending strength that meets the stringent operating environment requirements of IGBT modules, which is of great significance. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing reaction-sintered silicon nitride substrates to solve the problems raised in the prior art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a reaction-sintered silicon nitride substrate includes the following steps: S1: Slurry preparation: Add sintering aid, silicon powder, polyvinyl butyral, dispersant, plasticizer and carbon source to organic solvent, ball mill to obtain slurry; S2: Casting: The slurry is coated onto the film strip, dried, cast into a green body, and then cut to obtain the cast green body; S3: Powder coating: Boron nitride slurry is sprayed onto the cast green body to a powder coating amount of 0.05-0.3g / piece, thus obtaining a powder-coated cast green body; S4: Debinding: Stack 10-20 powdered cast green bodies in a frame and perform micro-positive pressure debinding to obtain debinded cast green bodies; S5: Nitriding and Sintering: The cast green film after debinding is nitrided and sintered, then naturally cooled and depressurized, surface treated and cleaned to obtain a reaction-sintered silicon nitride substrate.
[0007] Further, in step S1, the mass ratio of sintering aid, silicon powder, polyvinyl butyral, dispersant, carbon source and organic solvent is (3-5):(50-60):(3-5):(0.25-1.5):(0.25-1):(30-40).
[0008] Furthermore, the carbon source is prepared by mixing carbon powder and organic solvent in a mass ratio of 1:(5-10), dispersing it with external ultrasonic power of 200W-400W at 40-60℃ for 0.5-2h, and then ball milling it with silicon nitride balls at a speed of 50r / min-220r / min for 6-12h to obtain the carbon source.
[0009] Furthermore, the toner includes either nano-spherical toner or modified nano-spherical toner.
[0010] Further, the preparation method of the modified nanosphere carbon powder is as follows: place the nanosphere carbon powder in dilute nitric acid, mix well, stir and react at 40-60℃ for 20-60 min, filter, wash until neutral, and dry to obtain pretreated nanosphere carbon powder; modify the pretreated nanosphere carbon powder with N-(2-aminoethyl)-3-aminopropyltrimethoxysilane to obtain modified nanosphere carbon powder; The mass ratio of nano-spherical carbon powder to dilute nitric acid is 1:(20-30); the mass ratio of pretreated nano-spherical carbon powder to N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1:(0.3-0.9).
[0011] Furthermore, in step S2, the thickness of the cast green blank is 0.2-0.5 mm.
[0012] Further, in step S3, the boron nitride slurry is prepared as follows: dispersant, binder, and boron nitride powder are added to deionized water and stirred until homogeneous to obtain boron nitride slurry; The mass ratio of dispersant, binder and boron nitride powder is (0.25-0.5):(70-85):(14.5-20).
[0013] Furthermore, the boron nitride powder is pre-modified to obtain boron nitride-N-isopropylacrylamide composite powder, which is then used to prepare boron nitride slurry; The preparation method of the boron nitride-N-isopropylacrylamide complex powder is as follows: boron nitride nanosheets and urea in a mass ratio of 1:(5-10) are added to isopropanol, ball milled at 200-300 r / min for 24-72 h, filtered and washed, vacuum dried, and ground to obtain aminated boron nitride powder. Aminated boron nitride powder was added to anhydrous ethanol and ultrasonically dispersed. N-isopropylacrylamide, methylenebisacrylamide, and ammonium persulfate were then added. The mixture was reacted at 65-75℃ for 2-6 hours under nitrogen protection. After cooling to room temperature, the mixture was centrifuged, washed, and vacuum dried to obtain boron nitride-N-isopropylacrylamide composite powder. The mass ratio of aminated boron nitride powder, N-isopropylacrylamide, methylenebisacrylamide, and ammonium persulfate was 1:(3-5):(0.05-0.15):(0.05-0.1).
[0014] Furthermore, in step S4, the micro-positive pressure adhesive removal parameters are: the gas atmosphere is nitrogen, the air volume is 300-800L / min, the heating rate is 0.2-1℃ / min, the maximum temperature is 500-600℃, and the adhesive removal time is 12-24h. In step S5, the nitriding sintering includes a nitriding stage and a holding stage. The parameters for the nitriding stage are: heating rate of 2-5℃ / min, maximum temperature of 1150-1420℃, pressure of 0.5-2MPa, and nitriding time of 12-18h. The parameters for the holding stage are: heating rate of 2-5℃ / min, maximum temperature of 1800-1900℃, pressure of 0.5-2MPa, and holding time of 5-10h.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention introduces modified nanospherical carbon powder into the carbon source. First, compared to conventional carbon powder, nanospherical carbon powder has lower particle size and oxygen content, higher activity, and can react with the silicon nitride ceramic two-phase system, eliminating some of the excess two-phase system and improving thermal conductivity. Second, grafting diaminosilane onto the nanospherical carbon powder improves its interfacial compatibility with the slurry, thereby improving the slurry flowability in the casting process and reducing its adverse effects on the casting process. Finally, the modified nanospherical carbon powder enhances the interfacial bonding force with silicon powder and sintering aids, increasing the reduction nitriding reaction rate, reducing internal defects in the substrate, and improving the substrate density and mechanical properties.
[0016] 2. This invention introduces poly(N-isopropylacrylamide) onto the surface of boron nitride powder. First, boron nitride nanosheets are mildly modified with urea to enrich their surface with amino groups, which is beneficial for subsequent loading of poly(N-isopropylacrylamide). Second, N-isopropylacrylamide monomer is introduced into the aminated boron nitride powder. On the one hand, poly(N-isopropylacrylamide) increases the viscosity of the boron nitride slurry during room temperature spraying, preventing sagging and avoiding uneven coating of the boron nitride slurry on the surface of the cast green body, which increases scratches and vacuum defects and inhibits abnormal grain growth. On the other hand, during the subsequent debinding and nitriding process, the poly(N-isopropylacrylamide) on the surface of the boron nitride powder collapses and dissipates through pyrolysis upon heating, reducing the viscosity of the boron nitride slurry, promoting leveling of the boron nitride slurry, reducing substrate cracks, and thus improving the mechanical properties of the silicon nitride substrate.
[0017] 3. This invention combines specific nano-spherical carbon powder with casting process and gas pressure sintering, so that the prepared silicon nitride substrate can maintain high bending strength while improving thermal conductivity, thus breaking through the "seesaw effect" of bending strength and thermal conductivity in conventional preparation methods. Attached Figure Description
[0018] Figure 1 This is a process flow diagram of a reaction sintering silicon nitride substrate preparation method according to the present invention; Figure 2 This is a transmission electron microscope (TEM) schematic diagram of the spherical carbon powder in Embodiment 1 of the present invention; Figure 3 This is a schematic diagram of the particle size test of high-purity acetylene carbon black in Comparative Example 1 of the present invention. Figure 4 This is a schematic diagram showing the oxygen content of the spherical carbon powder in Example 1 of the present invention; Figure 5 This is a schematic diagram showing the oxygen content of high-purity acetylene carbon black in Comparative Example 1 of the present invention. Detailed Implementation
[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] In the following examples, the particle size of the nanosphere carbon powder is 50 nm; the parts are by weight.
[0021] Example 1: A method for preparing a reaction-bonded silicon nitride substrate: Step 1: Add 1 part of nano-spherical carbon powder to 6 parts of isopropanol, disperse it by external ultrasonication at 50°C and 300W power for 1 hour, and then ball mill it with silicon nitride balls at 120r / min for 12 hours to obtain the carbon source. S1: Add 1 part yttrium oxide, 1 part magnesium oxide, 55 parts silicon powder, 4 parts polyvinyl butyral, 1 part PMMA dispersant and 0.25 parts carbon source to 40 parts isopropanol, and ball mill with silicon nitride balls at 120 r / min for 12 h to obtain slurry; S2: The slurry is scraped onto the film tape, dried, and then cast into a green body with a thickness of 0.3 mm. It is then cut to obtain the cast green body. Step 2: Add 0.25 parts of sodium polycarboxylate, 75 parts of water-soluble phenolic resin, and 16 parts of boron nitride powder to deionized water, stir and mix well to obtain boron nitride slurry; S3: Spray boron nitride slurry onto the cast green body to obtain a powdered cast green body of 0.15 g / piece. S4: Stack 20 powder-coated cast green bodies in a frame, heat them to 600℃ at a rate of 0.8℃ / min under a nitrogen atmosphere and an air volume of 600L / min, and remove the glue under slight positive pressure for 24 hours to obtain the glue-removed cast green body. S5: The cast green blank with adhesive removal is sintered by heating to 1180℃ at a rate of 3℃ / min and nitriding at 1.2MPa pressure for 18h. Then, the temperature is increased to 1850℃ at a rate of 3℃ / min and held at 1.2MPa pressure for 8h. The temperature and pressure are then naturally reduced, and the surface is treated and cleaned to obtain the reaction sintered silicon nitride substrate.
[0022] Example 2: A method for preparing a reaction-bonded silicon nitride substrate: Step 1: Add 1 part of nano-spherical carbon powder to 6 parts of isopropanol, disperse it by external ultrasonication at 50°C and 300W power for 1 hour, and then ball mill it with silicon nitride balls at 120r / min for 12 hours to obtain the carbon source. S1: Add 1.5 parts of yttrium oxide, 1.5 parts of magnesium oxide, 55 parts of silicon powder, 4 parts of polyvinyl butyral, 1 part of PMMA type and 0.5 parts of carbon source to 40 parts of isopropanol, and ball mill with silicon nitride balls at 120 r / min for 12 h to obtain slurry; S2: The slurry is scraped onto the film tape, dried, and then cast into a green body with a thickness of 0.3 mm. It is then cut to obtain the cast green body. Step 2: Add 0.25 parts of sodium polycarboxylate, 75 parts of water-soluble phenolic resin, and 16 parts of boron nitride powder to deionized water, stir and mix well to obtain boron nitride slurry; S3: Spray boron nitride slurry onto the cast green body to obtain a powdered cast green body of 0.15 g / piece. S4: Stack 20 powder-coated cast green bodies in a frame, heat them to 600℃ at a rate of 0.8℃ / min under a nitrogen atmosphere and an air volume of 600L / min, and remove the glue under slight positive pressure for 24 hours to obtain the glue-removed cast green body. S5: The cast green blank with adhesive removal is sintered by heating to 1180℃ at a rate of 3℃ / min and nitriding at 1.2MPa pressure for 18h. Then, the temperature is increased to 1850℃ at a rate of 3℃ / min and held at 1.2MPa pressure for 8h. The temperature and pressure are then naturally reduced, and the surface is treated and cleaned to obtain the reaction sintered silicon nitride substrate.
[0023] Example 3: A method for preparing a reaction-bonded silicon nitride substrate: Step 1: Add 1 part of nano-spherical carbon powder to 6 parts of isopropanol, and disperse it by external ultrasonication at 50°C and 300W power for 1 hour. Then, it is ball-milled with silicon nitride balls at 120r / min for 12 hours to obtain the carbon source. S1: Add 1 part yttrium oxide, 1 part magnesium oxide, 50 parts silica powder, 3 parts polyvinyl butyral, 1 part PMMA dispersant and 0.75 parts carbon source to 30-40 parts isopropanol, and ball mill with silicon nitride balls at 120 r / min for 12 h to obtain slurry; S2: The slurry is scraped onto the film tape, dried, and then cast into a green body with a thickness of 0.3 mm. It is then cut to obtain the cast green body. Step 2: Add 0.25 parts of sodium polycarboxylate, 75 parts of water-soluble phenolic resin, and 16 parts of boron nitride powder to deionized water, stir and mix well to obtain boron nitride slurry; S3: Spray boron nitride slurry onto the cast green body to obtain a powdered cast green body of 0.15 g / piece. S4: Stack 20 powder-coated cast green bodies in a frame, heat them to 600℃ at a rate of 0.8℃ / min under a nitrogen atmosphere and an air volume of 600L / min, and remove the glue under slight positive pressure for 24 hours to obtain the glue-removed cast green body. S5: The cast green blank with adhesive removal is sintered by heating to 1180℃ at a rate of 3℃ / min and nitriding at 1.2MPa pressure for 18h. Then, the temperature is increased to 1850℃ at a rate of 3℃ / min and held at 1.2MPa pressure for 8h. The temperature and pressure are then naturally reduced, and the surface is treated and cleaned to obtain the reaction sintered silicon nitride substrate.
[0024] Based on Examples 1-3, the carbon source and boron nitride paste were optimized to further improve the mechanical strength and thermal conductivity of the silicon nitride substrate.
[0025] Example 4: A method for preparing a reaction-bonded silicon nitride substrate: Step 1: Place 1 part of nano-spherical carbon powder in 25 parts of dilute nitric acid, mix well, stir and react at 60°C for 45 min, filter, wash until neutral, dry, and obtain pretreated nano-spherical carbon powder. Step 2: Add 1 part of pretreated nanosphere carbon powder to an ethanol aqueous solution, mix by ultrasonication, add 0.6 parts of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, stir at room temperature for 3 hours, centrifuge, wash and dry to obtain modified nanosphere carbon powder. Step 3: Add 1 part of nano-spherical carbon powder to 6 parts of isopropanol, and disperse it by external ultrasonication at 50°C and 300W power for 1 hour. Then, it is ball-milled with silicon nitride balls at 120r / min for 12 hours to obtain the carbon source. S1: Add 1 part yttrium oxide, 1 part magnesium oxide, 55 parts silicon powder, 4 parts polyvinyl butyral, 1 part PMMA dispersant and 0.25 parts carbon source to 40 parts isopropanol, and ball mill with silicon nitride balls at 120 r / min for 12 h to obtain slurry; S2: The slurry is scraped onto the film tape, dried, and then cast into a green body with a thickness of 0.3 mm. It is then cut to obtain the cast green body. Step 4: Add 1 part boron nitride nanosheets and 6 parts urea to isopropanol, ball mill at 300 r / min for 48 h, filter, wash, vacuum dry, and grind to obtain aminated boron nitride powder. Step 5: Add 1 part of aminated boron nitride powder to anhydrous ethanol, ultrasonically disperse for 30 min, add 4 parts of N-isopropylacrylamide, 0.1 parts of methylenebisacrylamide and 0.05 parts of ammonium persulfate, react at 70℃ for 6 h under nitrogen protection, cool to room temperature, centrifuge and wash, vacuum dry to obtain boron nitride-N-isopropylacrylamide complex powder; Step 6: Add 0.25 parts of sodium polycarboxylate, 75 parts of water-soluble phenolic resin, and 16 parts of boron nitride powder to deionized water, stir and mix well to obtain boron nitride slurry; S3: Spray boron nitride slurry onto the cast green body to obtain a powdered cast green body of 0.15 g / piece. S4: Stack 20 powder-coated cast green bodies in a frame, heat them to 600℃ at a rate of 0.8℃ / min under a nitrogen atmosphere and an air volume of 600L / min, and remove the glue under slight positive pressure for 24 hours to obtain the glue-removed cast green body. S5: The cast green blank with adhesive removal is sintered by heating to 1180℃ at a rate of 3℃ / min and nitriding at 1.2MPa pressure for 18h. Then, the temperature is increased to 1850℃ at a rate of 3℃ / min and held at 1.2MPa pressure for 8h. The temperature and pressure are then naturally reduced, and the surface is treated and cleaned to obtain the reaction sintered silicon nitride substrate.
[0026] Comparative Example 1: A method for preparing a reaction-bonded silicon nitride substrate: S1: 1 part yttrium oxide, 1 part magnesium oxide, 55 parts silicon powder, 4 parts polyvinyl butyral and 1 part PMMA dispersant are added to 40 parts isopropanol and ball-milled with silicon nitride balls at 120 r / min for 12 h to obtain a slurry; S2: The slurry is scraped onto the film tape, dried, and then cast into a green body with a thickness of 0.3 mm. It is then cut to obtain the cast green body. The remaining steps are the same as in Example 1.
[0027] Comparative Example 2: A method for preparing a reaction-sintered silicon nitride substrate: Step 1: Add 1 part of high-purity acetylene black to 6 parts of isopropanol, and disperse it by external ultrasonication at 50°C and 300W power for 1 hour. Then, it is ball-milled with silicon nitride balls at 120r / min for 12 hours to obtain the carbon source. The remaining steps are the same as in Example 1.
[0028] Comparative Example 3: A method for preparing a reaction-sintered silicon nitride substrate: 1 part of nano-spherical carbon powder was placed in 25 parts of dilute nitric acid, mixed well, stirred at 60°C for 45 min, filtered, washed until neutral, and dried to obtain pretreated nano-spherical carbon powder. Step 2: Add 1 part of pretreated nano-spherical carbon powder to 6 parts of isopropanol, and disperse it by external ultrasonication at 50°C and 300W power for 1 hour. Then, it is ball-milled with silicon nitride balls at 120r / min for 12 hours to obtain the carbon source. The remaining steps are the same as in Example 4.
[0029] Comparative Example 4: A method for preparing a reaction-sintered silicon nitride substrate: Step 4: Add 1 part boron nitride nanosheets and 10 parts urea to isopropanol, ball mill at 300 r / min for 48 h, filter and wash, vacuum dry, grind to obtain aminated boron nitride powder. Step 5: Add 0.25 parts of sodium polycarboxylate, 75 parts of water-soluble phenolic resin, and 16 parts of boron nitride powder to deionized water, stir and mix well to obtain boron nitride slurry; The remaining steps are the same as in Example 4.
[0030] Testing: The slurry, cast green body, and silicon nitride substrate samples prepared in Examples 1-3 and Comparative Examples 1-2 were taken. The viscosity of the slurry was analyzed by rotational viscometer method; the solid content of the slurry and the solid content of the green body were analyzed by electronic weighing drying method; the Zeta potential of the slurry was analyzed by electrophoretic light scattering method; the density of the green body was tested by water displacement method; and the substrate performance was tested according to the national standard B / T45767-2025 method.
[0031] The substrate samples prepared in Examples 1, 4 and Comparative Examples 3-4 were tested for bending strength, thermal conductivity and coefficient of thermal expansion according to the method of national standard B / T 45767-2025.
[0032] The experimental data are shown in Tables 1 and 2 below.
[0033] Table 1 Performance test data of slurry, cast green body and substrate
[0034] Table 2 Performance test data of silicon nitride ceramic wafers after optimization of carbon source and boron nitride slurry
[0035] Conclusion: By optimizing the carbon source and boron nitride slurry composition, silicon nitride ceramic sheets can achieve higher insulation, thermal conductivity, and flexural strength.
[0036] In Comparative Example 1, the absence of nano-spherical carbon powder during slurry preparation resulted in reduced slurry viscosity, reduced solid content in the cast green blank, and reduced thermal conductivity of the aluminum nitride substrate.
[0037] In Comparative Example 2, high-purity acetylene black was used instead of nano-spherical carbon powder as the carbon source. The particle size and oxygen content of high-purity acetylene black are higher than those of nano-spherical carbon powder, which affects the high-temperature performance of the carbon source and thus reduces the mechanical properties, thermal conductivity and insulation of the silicon nitride substrate.
[0038] In Comparative Example 3, only the nano-spherical carbon powder was aminated, which reduced the compatibility between the nano-spherical carbon powder and the slurry, adversely affecting the casting process and ultimately reducing the mechanical properties and thermal conductivity of the silicon nitride substrate.
[0039] In Comparative Example 4, only the boron nitride powder was aminated, which increased the number of internal defects and cracks in the substrate, ultimately affecting the mechanical strength of the substrate.
[0040] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
Claims
1. A method for preparing a reaction-sintered silicon nitride substrate, characterized in that: S1: Slurry preparation: Add sintering aid, silicon powder, polyvinyl butyral, dispersant, plasticizer and carbon source to organic solvent, ball mill to obtain slurry; S2: Casting: The slurry is coated onto the film strip, dried, cast into a green body, and then cut to obtain the cast green body; S3: Powder coating: Boron nitride slurry is sprayed onto the cast green body to a powder coating amount of 0.05-0.3g / piece, thus obtaining a powder-coated cast green body; S4: Debinding: Stack 10-20 powdered cast green bodies in a frame and perform micro-positive pressure debinding to obtain debinded cast green bodies; S5: Nitriding and sintering: Nitriding and sintering are performed on the stripped green blank after debinding, followed by natural cooling and pressure reduction, surface treatment and cleaning to obtain reaction sintered silicon nitride substrate. The carbon source is prepared by mixing carbon powder in a mass ratio of 1:(5-10) with an organic solvent, dispersing it with external ultrasonic power of 200W-400W at 40-60℃ for 0.5-2h, and then ball milling it with silicon nitride balls at a speed of 50r / min-220r / min for 6-12h to obtain the carbon source. The toner includes either nano-spherical toner or modified nano-spherical toner. The modified nanosphere carbon powder is prepared by placing the nanosphere carbon powder in dilute nitric acid, mixing it, stirring and reacting at 40-60℃ for 20-60 min, filtering it, washing it until neutral, and drying it to obtain the pretreated nanosphere carbon powder. The pretreated nanosphere carbon powder was modified with N-(2-aminoethyl)-3-aminopropyltrimethoxysilane to obtain modified nanosphere carbon powder. In step S3, the boron nitride slurry is prepared as follows: dispersant, binder, and boron nitride powder are added to deionized water and stirred until homogeneous to obtain boron nitride slurry; The boron nitride powder is pre-modified to obtain boron nitride-N-isopropylacrylamide composite powder, which is then used to prepare boron nitride slurry. The preparation method of the boron nitride-N-isopropylacrylamide complex powder is as follows: boron nitride nanosheets and urea in a mass ratio of 1:(5-10) are added to isopropanol, ball milled at 200-300 r / min for 24-72 h, filtered and washed, vacuum dried, and ground to obtain aminated boron nitride powder. Aminated boron nitride powder was added to anhydrous ethanol and ultrasonically dispersed. N-isopropylacrylamide, methylenebisacrylamide and ammonium persulfate were then added. The mixture was reacted at 65-75℃ for 2-6 hours under nitrogen protection. After cooling to room temperature, the mixture was centrifuged, washed, and vacuum dried to obtain boron nitride-N-isopropylacrylamide complex powder.
2. The method for preparing a reaction-sintered silicon nitride substrate according to claim 1, characterized in that: In step S1, the mass ratio of sintering aid, silicon powder, polyvinyl butyral, dispersant, carbon source and organic solvent is (3-5):(50-60):(3-5):(0.25-1.5):(0.25-1):(30-40).
3. The method for preparing a reaction-sintered silicon nitride substrate according to claim 1, characterized in that: The mass ratio of nano-spherical carbon powder to dilute nitric acid is 1:(20-30); the mass ratio of pretreated nano-spherical carbon powder to N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1:(0.3-0.9).
4. The method for preparing a reaction-sintered silicon nitride substrate according to claim 1, characterized in that: In step S2, the thickness of the cast green blank is 0.2-0.5 mm.
5. The method for preparing a reaction-sintered silicon nitride substrate according to claim 1, characterized in that: The mass ratio of dispersant, binder and boron nitride powder is (0.25-0.5):(70-85):(14.5-20).
6. The method for preparing a reaction-sintered silicon nitride substrate according to claim 1, characterized in that: The mass ratio of aminated boron nitride powder, N-isopropylacrylamide, methylenebisacrylamide and ammonium persulfate is 1:(3-5):(0.05-0.15):(0.05-0.1).
7. The method for preparing a reaction-sintered silicon nitride substrate according to claim 1, characterized in that: In step S4, the micro-positive pressure adhesive removal parameters are: the gas atmosphere is nitrogen, the air volume is 300-800L / min, the heating rate is 0.2-1℃ / min, the maximum temperature is 500-600℃, and the adhesive removal time is 12-24h. In step S5, the nitriding sintering includes a nitriding stage and a holding stage. The parameters for the nitriding stage are: heating rate of 2-5℃ / min, maximum temperature of 1150-1420℃, pressure of 0.5-2MPa, and nitriding time of 12-18h. The parameters for the holding stage are: heating rate of 2-5℃ / min, maximum temperature of 1800-1900℃, pressure of 0.5-2MPa, and holding time of 5-10h.
8. A silicon nitride substrate prepared by a reaction sintering silicon nitride substrate preparation method according to any one of claims 1-7.